BATU NA PIR SITINJAK AS A CULTURAL TEXT: INTERPRETATIONS OF RITUAL AND FORM IN BATAK TOBA TRADITIONAL ART - Marfenas Marolop Sihombing; Ikhwanuddin Nasution; Agus Priyatno (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2026)
Batu Na Pir Sitinjak is a stone burial monument of the Batak Toba people that serves as a profound medium for cultural, spiritual, and social expression. This study aims to examine Batu Na Pir Sitinjak as a "cultural text" by interpreting its ritual practices and visual forms within the framework of traditional art. Employing a descriptive qualitative method, the research utilizes Hans-Georg Gadamer’s hermeneutic approach, which positions cultural artifacts as texts whose meanings are shaped through a dialogical relationship between tradition, historical context, and the interpreter’s experience. Data were gathered through field observations, visual documentation, and in-depth interviews with customary leaders. The findings reveal that the monument’s structure, which resembles a solu bolon (traditional boat), symbolizes the soul's transition to the ancestral realm. Dominant visual elements, including oversized head sculptures representing sahala (spiritual power) and seated figures reflecting submission, indicate the ancestor’s social and spiritual status. Furthermore, gorga ornamentation serves as a symbolic language for Batak cosmology, while the figure of a woman holding bowls represents the panghurasan (purification) ritual and the vital role of women as spiritual agents. This study concludes that Batu Na Pir Sitinjak is not merely a historical relic but a dynamic cultural text. Its meaning is continually reconstituted through the "fusion of horizons," where aesthetic, ritual, and social values remain alive and reinterpreted within the ongoing relationship between the living and their ancestors. Keywords: Batu Na Pir Sitinjak; cultural text; Gadamerian hermeneutics; Batak Toba customary rituals; traditional art